Elementy moralne w sporcie i ich medialne odzwierciedlenie - Tarczyński, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2025)
Sport, as a social phenomenon, presupposes the existence of rules and norms governing the behaviour of human individuals. In addition to technical or customary rules, in sport – as in any sphere of human activity – we also deal with values and moral rules. In turn, the formulation of moral rules in the form of duties, given with appropriate justification, results in ethics – general or specific, if it refers to a distinguished area of life. The text is devoted to selected ethical problems occurring in competitive sport. At the same time, the approach adopted in the text takes account of the fact that reports from the sports arena, the general image of sport as such (and the problems arising in it) and, finally, its popularity itself, are nowadays to a significant extent the result of the action of the mass communication media, which in turn also affects the moral condition of society. Social practice, its media image and moral awareness (i.e. people’s beliefs and principles) form an interconnected whole.